2019
DOI: 10.1002/elan.201900288
|View full text |Cite
|
Sign up to set email alerts
|

2D MXenes as Perspective Immobilization Platforms for Design of Electrochemical Nanobiosensors

Abstract: MXenes are a new group of 2D nanomaterials with fascinating properties including high electrical conductivity, hydrophilic nature, easily tunable structure and high surface area. This is why MXene modified interfaces are extremely promising for the preparation of sensitive electrochemical biosensors. While there are numerous reports on MXene‐based enzymatic biosensors for detection of a wide range of analytes, application of MXene for construction of affinity biosensors is in its infancy. The review article su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…Such materials possess interesting properties such as high electrical conductivity and thermal stability, hydrophilic characteristics, and a high surface area [ 26 ]. These materials have applications mainly in energy storage [ 27 , 28 ], sensing [ 29 ], electromagnetic shielding [ 30 , 31 ], water technologies [ 32 ], and biomedicine [ 33 , 34 ]. The most commonly studied and accessible is Ti 3 C 2 T x , which is one of the most promising materials for photothermal conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Such materials possess interesting properties such as high electrical conductivity and thermal stability, hydrophilic characteristics, and a high surface area [ 26 ]. These materials have applications mainly in energy storage [ 27 , 28 ], sensing [ 29 ], electromagnetic shielding [ 30 , 31 ], water technologies [ 32 ], and biomedicine [ 33 , 34 ]. The most commonly studied and accessible is Ti 3 C 2 T x , which is one of the most promising materials for photothermal conversion.…”
Section: Introductionmentioning
confidence: 99%
“…MXenes, the innovative 2D derivatives of MAX phases precursors ( M =transition metal, A =an A‐group element, X =C and/or N), are ideal candidates for a number of non‐limited applications including electromagnetic shielding, energy storage, environmental remediation, catalysis etc . MXenes are also regarded as multifunctional nanomaterials used as suitable platforms in biosensing due to their adsorptive properties, biocompatibility, hydrophilicity, strong absorbance in the near‐infrared region and interesting redox behaviour …”
Section: Electrochemical Exosome Biosensingmentioning
confidence: 99%
“…Several breakthroughs in MXene synthesis and MXene-nanocomposite preparation resulted in various elemental compositions and surface functional tunabilities (Khazaei et al, 2019). During the last few years, MXenes have played an ever important role in terms of both crystalline and composition varieties for catalysis (Zhang et al, 2018;Benchakar et al, 2019;Li and Wu, 2019;Sun et al, 2019), environmental applications (Rasool et al, 2019), development of Li batteries (Ostadhossein et al, 2019;, and (bio)sensors (Kalambate et al, 2019;Lorencova et al, 2019;Mohammadniaei et al, 2019;Wu Q. et al, 2019;Gajdosova et al, 2020;Szuplewska et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In our recent review paper, we showed that although there are numerous enzyme-based electrochemical biosensors, development of affinity-based electrochemical biosensors is still in its infancy (Lorencova et al, 2019 ). We believe that in order to successfully develop sensitive and selective affinity-based electrochemical biosensors, particular attention needs to be paid to interfacial modification of MXene (Lorencova et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation